Nudging - Ahmad Taleb; Ameen Talib (Indonesian Journal of Social Science Research, 2020)
Several challenges and rising costs are facing the healthcare industry today. Some of these health costs are a direct consequence of lifestyle choices such as unhealth diets, obesity and smoking. These challenges can be managed if policy makers have the tools to influence and alter people’s behaviour. The conventional tools used for influencing behaviour include legislation, regulation and information provision. Recently, interest has been shown in policies that ‘nudge’ people in particular directions.